2013
DOI: 10.4028/www.scientific.net/amr.634-638.3770
|View full text |Cite
|
Sign up to set email alerts
|

Illumination Design of the Computer Classroom

Abstract: This paper carries on an illumination design about the computer classroom of Architecture and Civil Engineering College, Taiyuan University of Technology according to the rules of intensity of illumination standard value and lighting power density (LPD) stipulated in the Building Illumination Design Standard (GB50034-2004), and puts forward a feasible project in theory. In accordance with the test and subjective evaluation, it also puts forwanrd the effectiveness and feasibility of the lighting design project … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…For example, a person starts working without a work permit, which results in an accident. In a study by Cong GP (2013), it was concluded that inspection can reduce cost and human casualties in process industries and improve the performance of safety systems [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a person starts working without a work permit, which results in an accident. In a study by Cong GP (2013), it was concluded that inspection can reduce cost and human casualties in process industries and improve the performance of safety systems [ 30 ].…”
Section: Discussionmentioning
confidence: 99%